Artificial Boundary Conditions for "Vortex in Cell" Method (Journal of Computational Mathematics, 2003)
This paper mainly designs artificial boundary conditions for "vortex in cell" method in solving two-dimensional incompressible inviscid fluid under two conditions: one is with periodical initial value in one direction and the other with compact supported initial value. To mimic the vortex motion, Euler equation is transformed into vorticity-stream function and the technique of vortex in cell is applied incorporating with the artificial boundary conditions.
Keywords: Incompressible inviscid flow; Vortex in cell method; Artificial boundary condition.